STRATEGI KOMUNIKASI DEWAN PIMPINAN DAERAH PARTAI PERSATUAN INDONESIA (DPD PARTAI PERINDO) DALAM MELAKUKAN PENCITRAAN DI KOTA PEKANBARU - Regina Emsi; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Partai Persatuan Indonesia (Partai PERINDO) is a newly established political party and has never participated as a participant in the general elections held in Indonesia. The establishment of the Indonesian Persatuan Party (PERINDO Party) started with the establishment of the Association of Indonesian Unity Society (ORMAS PERINDO) officially established on February 23, 2013. Approximately 2 years after the founding of the Persatuan Indonesia Society (ORMAS PERINDO), on February 7, 2015 Persatuan Indonesia (Partai PERINDO) is officially established. The Regional Council of the Partai Persatuan Indonesia (DPD PERINDO Party) Pekanbaru Town which is structurally at the district / city level should not only wait for the communication strategy conducted by the Central Executive Board of the Partai Persatuan Indonesia (DPP PERINDO Party) in the image of Partai Persatuan Indonesia PERINDO) to gain sympathy in the midst of society. The formulation of this research problem, how is the communication strategy of the Regional Leadership Council of the United Indonesia Party (DPD Party PERINDO) in imaging in Pekanbaru City?